To find the quotient when dividing \( 56r - 12 \) by \( 4t \), we can break it down as follows:
- Divide each term in the numerator \( 56r - 12 \) by \( 4t \):
\[ \frac{56r}{4t} - \frac{12}{4t} \]
- Simplify each term:
\[ \frac{56r}{4t} = \frac{56}{4} \cdot \frac{r}{t} = 14 \cdot \frac{r}{t} = \frac{14r}{t} \]
\[ \frac{12}{4t} = \frac{12}{4} \cdot \frac{1}{t} = 3 \cdot \frac{1}{t} = \frac{3}{t} \]
- Combine the simplified terms:
\[ \frac{14r}{t} - \frac{3}{t} = \frac{14r - 3}{t} \]
Therefore, the final result when dividing \( 56r - 12 \) by \( 4t \) is:
\[ \frac{14r - 3}{t} \]
Thus, the correct response is:
14r−3t (Start Fraction 14 r minus 3 over t End Fraction).